Age and Sex Correlation with WHO Clinical Stages of HIV-1 Patients in Khartoum State, Sudan 2020 - Nafisa A Dawood,; Khalid A Enan,; Mahdi M Yagoup,; Waleed A Hussein,; Wafa I Elhag, (International Journal of Scientific Research in Science and Technology, 2024)
Background: The World Health Organization (WHO) clinical staging system for Human Immunodeficiency Virus (HIV) infection has been widely used in developing countries, especially in Africa, where there is no access to laboratory services and where it is not possible to assess the disease status using CD4+ T-lymphocyte counts.Objective: This study aimed to detect the WHO clinical stages of HIV-1 patients in ART for 12±3 months attending different Voluntary counseling, testing, and treatment centers (VCT/ART) centers in Khartoum state, Sudan.Methods: Data were obtained from 110 HIV-1 patients by a direct interviewing questionnaire, and information on WHO clinical staging was collected retrospectively on-site from patient records, then analyzed by Chi-squared test using SPSS version 21Results: Most of WHO clinical stage 3 HIV-1 patients were males 56.7% (34/60), and the majority of them belonged to the age group 19-39 years 53.3% (32/60), followed by the age group 40-59 years old and 60-89 years old with percentage 36.7% (22/60) and 10% (6/60) respectively.Conclusion: A significant relationship was obtained between age and WHO clinical stages, whereas there is no relationship with sex.
Keywords: Africa; HIV-1; Sudan; WHO Clinical Stages